Acupuncture and moxibustion for endometriosis: A systematic review and analysis - Yongxia Wang; Meaghan E. Coyle; Miaowen Hong; Siya He; Anthony L. Zhang; Xinfeng Guo; Chuanjian Lu; Charlie C.L. Xue; Xuefang Liang (Elsevier, 2023)
Objectives: This study aimed to examine the effect of acupuncture on symptoms and health-related quality of life in patients with endometriosis. Methods: Nine biomedical databases were searched to April 2022 to identify randomized controlled trials of acupuncture and/or moxibustion used alone or as adjunct to guideline-recommended pharmacotherapy for the treatment of endometriosis. One reviewer extracted data and another verified the data. A random effects model was used to calculate mean differences. Results: Fifteen trials involving 1018 patients met the inclusion criteria, but diversity in comparisons and outcome measures prevented meta-analysis. Compared to sham acupuncture, manual acupuncture was more effective at reducing dysmenorrhea VAS pain score (mean difference [MD] − 2.40, 95 % CI [− 2.80, − 2.00]; moderate certainty evidence), pelvic pain VAS score (MD − 2.65, 95 % CI [− 3.40, − 1.90]; high certainty evidence) and dyspareunia VAS scores (MD − 2.88, [− 3.83, − 1.93]), lessened the size of ovarian cyst (MD − 3.88, 95 % CI [− 7.06, − 0.70]), and improved quality of life. Compared to conventional therapy, manual acupuncture plus conventional therapy and warm needle alone resulted in greater improvements in quality of life than conventional therapy. Among the six studies that reported safety, fewer adverse events were reported in participants who received acupuncture or moxibustion. Conclusions: Low to moderate certainty evidence from single studies showed that manual acupuncture may improve pain-related symptoms and quality of life; however, there is insufficient evidence on the overall effectiveness of acupuncture and moxibustion for endometriosis.